Length–weight relationships comparison between juveniles and adults of fish species from the mangroves of south Brazil - Bianca Possamai; Ana Carolina dos Passos; Bárbara Maichak de Carvalho (Acta Scientiarum. Biological Sciences, 2020)
This study reports the length‐weight relationships (LWRs) for 8 fish species that inhabit mangroves. Many fisheries depend on mangroves, which serve as nursery and feeding areas for the juvenile stage of fishes, shrimp, and other fishery resources. In this sense, mangroves provide many ecosystem services, therefore increasing the basic biological knowledge of these ecosystems can help to understand their functioning and create conservation strategies. The majority of LWR studies do not consider juveniles, and it is important to consider these differences as juveniles can grow differently from adults. The fishes were collected from Perequê mangrove, Paraná, Brazil between 2008 and 2010. A variety of fishery gears were employed, including trammel nets, fyke nets, and traps made with plastic bottles combined with four baits. The specimens were measured (weight and length), sexed and evaluated for maturational stage. For the adults, the LWRs were calculated separately by the sex, while juvenile LWRs were estimated together. In general, there were differences in growth type between sexes and life stages. Some species showed differences compared to FishBase estimations, but this could be due to the lengths (and life stage) of the individuals used in the present study compared to FishBase. The discrepancies between adult, juvenile and FishBase estimations showed the importance of considering these aspects in studies using LWR.